Penerapan Model Discovery Learning Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas VI SDN Leseng Moyo Hulu - Wiwi Noviati; Eryuni Ramdhayani; Supratman Supratman (Peneliti.net, 2022)
The teacher centered learning causes students to be less active in learning so that students do not understand the material presented by the teacher. This causes low student learning outcomes. The discovery learning model is one alternative to overcome these problems. This study aims to determine the improvement of science learning outcomes of class VI SD LESENG MOYO HULU through the application of the discovery learning model. This research is a classroom action research. This classroom action research consists of stages of planning, action, observation and reflection. The subjects in this study were students of class VI SD LESENG MOYO HULU, totaling 25 students. Data collection techniques using documentation, observation and test. The data analysis technique in this research is descriptive qualitative and quantitative. Based on the results of the analysis of the learning outcomes test, the classical mastery in the first cycle was 48% and increased to 92%. This shows that student learning outcomes increase after being taught with the discovery learning models